The increased basic fibroblast growth factor expression and osteoblasts number post Bifidobacterium bifidum probiotic supplementation during orthodontic tooth movement in Wistar rats. - Ari Triwardhani; Citra Anggitia; I Gusti Aju Wahju Ardani; Alexander Patera Nugraha; Wibi Riawan (GarVal Editorial Ltda., 2021)
Context: Bifidobacterium bifidum as a beneficial probiotic may regulate the inflammation and induce the bone remodeling by enhancing osteoblasts and basic fibroblast growth factor (bFGF) expression in the tension side of alveolar bone during orthodontic tooth movement (OTM). Aims: To evaluate the expression of bFGF and the number of osteoblasts during OTM after B. bifidum probiotic supplementation in male Wistar rats. Methods: Wistar rats (n = 42) were divided into 6 groups (n = 7) accordingly as follow: OTM and phosphate buffer saline (PBS) for 3 days (K3); OTM and PBS for 7 days (K7); OTM and PBS for 14 (K14); OTM and B. bifidum for 3 days (P3); OTM and B. bifidum for 7 days (P7); OTM and B. bifidum for 14 days (P14). OTM was established by NiTi close coil spring with 10 g force-placed between the first incisor and the first maxillary molar of Wistar rat. The samples were then terminated on days 3, 7, and 14. The maxillary tissue was isolated for the immunohistochemical examination and hematoxylin-eosin staining. All data were analyzed by using an independent t-test (p<0.05), which was implemented based on Kolmogorov-Smirnov and Levene's test (p>0,05). Results: The highest bFGF expressions and osteoblast numbers were found in Group P14. There were significant differences in bFGF expression and osteoblast numbers in the tension side of alveolar bone during OTM between the control and treatment groups (p<0.05). Conclusions: The post supplementation of B. bifidum shows the enhancement of bFGF expression, and osteoblast number in the tension side of alveolar bone during OTM determined immunohistochemically.